Seeing, Believing, and Learning to Be Skeptical: Supporting Language Learning Through Advertising Analysis Activities. Issue 3 (22nd August 2014) - Hobbs, Renee; He, Haixia; Robbgrieco, Michael
<x xml:space="preserve">Abstract</x> This study documents how a high school ESL teacher working with new immigrants ages 14–20 supported the development of their critical thinking and English language skills by using advertising analysis activities. The article examines the use of key critical questions for analyzing media messages and documents instructional activities designed to strengthen students' vocabulary, reading, and discussion skills to build inferential thinking and critical analysis skills. The researchers focus on four instructional practices used by the participating teacher, which rely on strategies for applying critical questions to analyze advertising: the cloze technique, the question generation approach, practice in analyzing ads using critical questions in class discussion, and a collaborative online writing activity resulting in the creation of a multiparagraph multimedia document. These activities provided a meaningful opportunity for students to practice speaking, listening, reading, and writing skills in English while supporting the development of abstract thinking, balancing the learning of new academic language and cultural knowledge, and connecting with students' prior knowledge, home cultures, and everyday experience.